(untitled) (AYUSHDHARA, 2017)
In spite of advanced chemotherapy and radiotherapy the term Cancer still induces fear of death in common man. Cancers figure among the leading causes of morbidity and mortality worldwide, with approximately 14 million new cases and 8.2 million cancer related deaths (2012). Generally in the women, the five most common sites of cancer are breast, colorectum, lung, cervix, and stomach. But, the most common types of gynaecologic malignancies are cervical cancer, ovarian cancer, and endometrial (uterus) cancer etc. On par with other cancers, Gynecological cancers also contribute to significant number of deaths. In India alone, among the gynaecological cancers, breast cancer accounts for 21.5% deaths; cervical cancer for 20.7% deaths, ovarian cancer for 6.0% of deaths (World Health Organization - Cancer Country Profiles, 2014). The main goals of a cancer diagnosis and treatment programme are to cure or considerably prolong the life of patients and to ensure the best possible quality of life to cancer survivors. Ayurveda plays a key role in prevention; prolong the life span and improvement of quality of life in cancer. In the direction of prevention of cervical carcinoma, poly-herbal compounds ‘Praneem’ and ‘Basant’ are studied extensively. To improve the quality of life, CCRAS have been initiated trials with coded drug AYUSH-QOL-2C, in non-metastatic breast cancer patients those who are receiving chemotherapy/radio-therapy, at St. Johns medical college, Bangalore, Karnataka. Some other clinical studies are also carried out to see the effect of turmeric as an adjuvant in abroad. Apart from the clinical trials number of single herbal drugs like Haridra, Bhallataka, Ashvagandha etc., and compound herbo-mineral preparations are studied to see their efficacy on different types of gynaecological cancers. In united states of America, clinical trials on arsenic preparations are also carried out. Present article aims to review the usefulness of these drugs in Gynecological cancers and their safety too.